The effect of magnesium alone or its combination with other supplements on the markers of inflammation, OS and metabolism in women with polycystic ovarian syndrome (PCOS): A systematic review - Li, Ruiyun; Li, Zhiyuan; Huang, Yi; Hu, Kaiyan; Ma, Bin; Yang, Yuan (Frontiers in Endocrinology, 2022)
The objective of this systematic review is to synthesize the available evidence on the effectiveness of magnesium supplements on the markers of inflammation, oxidative stress (OS), and metabolism in PCOS patients and to provide a basis for its clinical treatment. Electronic databases (PubMed, Cochrane Library databases, Embase, Web of science, CMB, CNKI, VIP, Wan Fang and ClinicalTrials.gov) were searched from their inception until January 2022. Randomized controlled trials (RCTs) for PCOS undergoing therapy with magnesium supplementation alone or in combination with other agents. The primary outcomes were the markers of blood glucose and OS. 363 patients from nine RCTs were included in the current systematic review. Four of the nine studies reported the effects of magnesium supplementation alone on OS or metabolic markers in women with PCOS. While magnesium supplementation alone did not show any significant improvement in the markers of inflammation, OS or metabolism in PCOS, seven of the nine articles reported the effect of magnesium co-supplementation on OS or metabolic markers in PCOS patients. Magnesium combined with vitamin E or zinc-calcium-vitamin D significantly improved glucose and lipid metabolism in PCOS patients. Magnesium intake alone did not lead to a significant improvement in the markers of OS, blood glucose, or serum lipids in PCOS. However, magnesium combined with other supplements (vitamin E, zinc, zinc-calcium-vitamin D) significantly improved serum hs-CRP, insulin, HOMA-IR, TG, TC levels, and the improvement in OS markers was inconclusive. The effect of magnesium and melatonin supplementation on the markers of metabolism needs to be further verified.